Cell-Free Fetal DNA for Prenatal Screening of Aneuploidies and Autosomal Trisomies: A Systematic Review - Kenza Benchekroun Belabbes; Elena Bendala Tufanisco; Chirag C. Sheth (Hindawi Limited, 2024)
Conclusion: Cell-free fetal DNA is a reliable screening tool for autosomal trisomies. It is also useful for sex chromosome aneuploidies, although the positive predictive values are lower. A positive screening result should be followed with a confirmatory test.